Frequently asked questions about overscheduling and stress - Harmon, Daniel E. (New York : Rosen Pub., 2010)
Offers teens an overview of the symptoms and potential dangers associated with overscheduling and stress, explaining the mental, physical, and emotional problems that can stem from stress; and describing ways to control and maintain healthy stress levels.
What are overscheduling and stress? -- Why can't you have a life? -- When do overscheduling and stress begin to affect you? -- What are the long-term effects? -- How can you control stress?
Includes bibliographical references (p. 60-61) and index.
4.7
Young Adult.
Young Adult
Keywords: Stress in adolescence -- Juvenile literature; Stress management for teenagers -- Juvenile literature; Stress (Psychology); Stress management; Stress (Psychology); Stress management